On Generalization of Fejer Type Inequalities - Delavar, Mohsen Rostamian; Sen, M. De La (Communications in Mathematics and Applications, 2017)
Some generalizations of Fejér type inequalities related to \(η\)-convex functions are investigated. Also applications for trapezoid and mid-point type inequalities are given.